Tańczące muzy. Kino i korespondencja sztuk - Hendrykowski, Marek (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2009)
Dancing muses. Cinema and the correspondance of arts How traditional arts are used and adapted by film? In what ways do they correspond and cooperate as structural elements supporting a fully coherent piece of film? These fundamental questions open many areas of film research. The paper examines three competing definitions of cinema as polimorfic art and gives overview of various versions and modes of coexistence of arts in film. Author argues that ambivalence is evidenced between policy of adapting established arts and policy of modelling new art by filmmakers. The role of film practice in orchestrating individual strategies is used to highlight this ambivalence. Aspirations good for one separate art can be wrong for film as specific medium and kind of art. „The play’s the thing”. As far as symbiosis of many different arts is important for cinema, culture of adaptation remains key question in film practice and filmmaking.